Revisiting the Diurnal Pulses of Tropical Cyclones Over the Northwest Pacific Ocean - Jinjing Zhang; Yu Du (Geophysical Research Letters, 2025)
Abstract This study investigates the characteristics and mechanisms of diurnal pulses (DPs) in tropical cyclones (TCs) over the Northwest Pacific. Previous studies have noted discontinuities in DP propagation with respect to radius, but lacked an explanation for this phenomenon. Our findings reveal that this discontinuity results from the superposition of an outward‐propagating mode driven by inertial‐gravity waves and quasi‐phase‐locked signals associated with the diurnal variations in the TC secondary circulation. DP occurrence exhibits strong latitude dependence. DPs occur more frequently within 0°–30°N latitude, likely driven by inertial‐gravity waves originating from the TC inner core at the tropopause. North of 30°N, DP propagation is primarily influenced by the TC outflow winds, with the DP propagation speed strongly correlated to outflow strength. Additionally, DPs share similarities in characteristics and mechanisms with the offshore propagation of coastal rainfall, both governed by inertial‐gravity waves in lower latitudes and by wind advection at higher latitudes.